Smart steering lock security system / Khairul Anwar Ibrahim & Mohd Hussamuddin Salehuddin - Ibrahim, Khairul Anwar; Salehuddin, Mohd Hussamuddin (2015)
In this project, a magnetic steering lock device with the security password system is create. Nowadays, usually the steering lock devices will use a key to lock and unlock it. Thus, this project will create a steering lock design that have a security password. The model is build to improve the security level of the steering lock device compare to the steering lock that use a key to lock and unlock it. It use a relay as a contact with the magnetic plate to either lock and unlock the steering lock. In order to run the program, we use programming coding, MPLABX software and the Proteus software. This project will use a PIC as a controller to the input and output of the circuit. It will control the relay whether to unlock or remain lock the door with magnetic lock. As the steering lock device is on, the current will cause the relay to have a contact with the magnetic plate and will lock the steering lock until the correct password is entered. The intelligent device which performs task is a microcontroller. 4x4 keypad, magnetic steering lock system is interface to Microcontroller. The microcontroller continuously monitor the keypad input and locks unlocks the magnetic steering lock system when a correct password is given. The microcontroller is loaded with intelligent program written using embedded 'C' language.